Effect of Intense Pulsed Light to Mitigate Meibomian Gland Dysfunction for Dry Eye Disease - Suwal, Abhishek; Hao, Jilong; Liu, Xiufen; Zhou, Dandan; Jia, Zhifang; Liu, Hongwei; Ren, Yu; Shao, Fei; Lu, Chengwei (Klinische Monatsblätter für Augenheilkunde, 2022)
Background This retrospective study aimed to evaluate the effect of intense pulsed light treatment (IPL) combined with meibomian gland expression (MGX) in treating meibomian gland dysfunction (MGD) related dry eye disease (DED) for the first time in Northeast China.Methods Thirty-one MGD-related dry eye patients were managed by IPL-MGX from October to December 2019 in The First Hospital of Jilin University. Those patients had single IPL-MGX treatment with one follow-up visit, and no topical eye drops used were included in the study. General checkup and data collection helped in determining the age, sex, diagnosis, status of the MG, first noninvasive tear break-up time (1st NIBUT), average NIBUT, the height of tear film, and additional medical history.Results There was an improvement in the function of the meibomian gland (MG), with a significant decrease in the MG dropouts in the upper eyelid (Rt eye, p = 0.0047; Lt eye, p = 0.0158) and lower eyelid (Rt eye, p = 0.0017; Lt eye, p = 0.0027) plus the average NIBUT (Rt eye, p = 0.0264) also showed improvement after the IPL-MGX treatment. Though no significant difference was reached with the average NIBUT of the Lt eye (p = 0.5256) and the NIBUT grade (Rt eye, p = 0.0578; Lt eye, p = 0.0588), there was an increased duration of the average NIBUT and improved NIBUT grading. The negative results may be because of the maximum severity of DED and the limited treatment times.Conclusions The result suggests that IPL-MGX was effective in treating MGD-related DED.
Keywords: dry eye disease (DED); meibomian gland dysfunction (MGD); noninvasive tear break-up time (NIBUT); intense pulsed light (IPL)